Long-run Effects of Market Risk Factors on Bank Performance in the SSA Banking System - Zheng, Changjun; Jean-Petit, Sinamenye (European Scientific Journal, ESJ, 2021)
The study assesses the long-term effects of market risk factors on bank performance in the Sub-Saharan Africa banking system. The article identifies the most influential market risk factor and the most affected bank performance factors in the long term. It covers 40 countries with 350 commercial banks for ten years. The analysis uses dynamic fixed-effects models (ARDL-DFE). The results demonstrated that non-performing loans are the most influencers affecting bank performance factors in the long run. Furthermore, the results show that return on average assets is the most bank performance factor affected mainly by market risks, especially the NPLs in the long run. Finally, the findings surprisingly proved mutual interactions and cointegration movements among bank market risk factors and bank performance measures in the long run. These findings can assist central banks in supervising and regulating SSA commercial banks and inspire regional bank managers in reducing market risks and sharpening long-run performance strategies through resource reallocating.